The taxonomic identity of Ophiorrhiza rarior and O. mycetiifolia (Rubiaceae) - Wu, Lei; Hareesh, Vadakkoot-Sankaran; Yu, Yun-Lin (Phytotaxa, 2017)
Through field observations, recollections at known sites and research on specimens and relevant literature, Ophiorrhiza rarior and O. mycetiifolia are reduced to the synonyms of O. amplifolia. In addition, lectotype of Ophiorrhiza amplifolia is here designated with detailed description, colour photographs, conservation status and distribution map.